Brillouin echo-distributed sensing based on differential phase-shift keying technique - Lee, Min Won; Stiller, Birgit; Hauden, Jérôme; Maillotte, Hervé; Thévenaz, Luc; Sylvestre, Thibaut (European Conference on Optical Communication, ECOC, 2011)
In this letter, we demonstrate experimentally Brillouin echo-distributed sensing based on differential phase-shift keying technique. A positive and negative pulse is applied to a single Mach-Zehnder modulator to achieve a resolution of 5 cm. © 2011 OSA.
CRIS-Team Scopus Importer:2021-06-29